PENGARUH PARTISIPASI STAKEHOLDER TERHADAP KUALITAS KEPUTUSAN KEBIJAKAN SEKOLAH - Darlina, Nella; Prianti, Nila; Marsidin, Sufyarma; Irsyad, Irsyad (STKIP Pesisir Selatan, 2025)
In many communities, the public plays a role in providing input on school environmental safety, local culture that must be respected, and financial or non-financial support through collaboration between the community and schools. This study reviews the latest literature (2015–2025) on the influence of stakeholder participation on the quality of school policy decisions, with a particular focus on the involvement of teachers, students, and the community. Through a systematic literature review, this article synthesises empirical findings and conceptual studies on participation mechanisms, supporting/inhibiting factors, and impacts on decision quality (sustainability, relevance, legitimacy, and implementability). The results show that meaningful participation—not just a formality—increases the legitimacy and relevance of policies and the probability of successful implementation. However, the effectiveness of participation depends on the capacity of actors, school governance structures, access to information, and a collaborative culture. This article concludes with recommendations for practice and directions for further research.